Harmonic control in electrical drives for transport systems - Nguyen, Thanh Lich; Phung, Van Trang (International Journal of Power Electronics and Drive Systems (IJPEDS), 2025)
Field-oriented control (FOC) is the most widely used method for controlling alternating current (AC) drives, using Clarke and Park transformations to enable current controllers to manipulate the amplitude of the fundamental component of the phase currents. The inherent advantage of the FOC method is that it transforms current control tasks into a DC domain, thereby enhancing the dynamics of current response and the capability of tracking the current reference. The idea of the FOC can be extended beyond the fundamental component to control some of the harmonics buried in any signals presented in electrical drives, which is particularly critical in transport systems. This paper presents a harmonic control framework, optimized for transport applications, with three different topologies: adaptive linear neural (Adaline), resonant controller (RC), and harmonic controller (HC). The study provides a comprehensive theoretical analysis of the mathematical relationships between these three control structures. Additionally, it explores the application of harmonic controllers in both current and speed control loops. Simulation and experimental results are used to validate the proposed framework, demonstrating its potential to improve the performance of electric drives in vehicles, including enhanced energy efficiency, reduced electromagnetic interference, and smoother torque production.